Management compensation and the managerial labor market - Jensen, Michael C.; Zimmerman, Jerold L. (Journal of Accounting and Economics, 1985)
The papers in this volume and briefly summarized in this introduction document that: (1) executive compensation is positively related to share price performance: (2) poor firm performance is associated with increased executive turnover; (3) managers choose accounting accruals in ways that increase the value of their bonus awards; (4) the adoption of new short- and long-term executive compensation plans and golden parachutes are associated with positive share price reactions; (5) the death of a firm's founder is associated with positive share price reactions; and (6) managers are less likely to make merger bids that lower their stock prices when they hold more stock in their firm. These findings are interpreted as generally supporting the view that executive compensation packages help align managers' and shareholders' interests.